Combining experiments and computations to understand the intercalation potential and redox mechanism for A2Ti3O7 (A=Li, Na). Issue 1740 (20th March 2015) - Morales-García, A.; Arroyo-de Dompablo, M. Elena; Rousse, A. G.; Senguttuvan, P.; Tarascon, J.-M.; Rosa Palacín, M.
ABSTRACT: Na2 Ti3 O7, a potential negative electrode for Na batteries, is investigated by combining experiments and first-principles calculations at the Density Functional Theory (DFT) level. A structural model is proposed for the reduced phases ( A 2+x Ti3 O7 ), with all alkali ions in octahedral coordination, leading to a distorted rocksalt type structure. The calculated elastic constants support the mechanical stability of the proposed Na4 Ti3 O7 structure. Calculated average intercalation potentials are 0.37 V for Na insertion in Na2 Ti3 O7 and 1.46 V for Li insertion in Li2 Ti3 O7, being in very good agreement with the values observed experimentally (0.3 V and 1.6 V respectively). The higher polarizing character of Li ions vs Na ions acts as a key-factor to bring the Li intercalation voltage 0.7 V above that of Na intercalation in layered- A 2 Ti3 O7 materials.